Graphene two-dimensional crystal prepared from cellulose two-dimensional crystal hydrolysed from sustainable biomass sugarcane bagasse. (20th December 2019) - Long, Si-Yu; Du, Qi-Shi; Wang, Shu-Qing; Tang, Pei-Duo; Li, Da-Peng; Huang, Ri-Bo
Abstract: In this study, a sugarcane bagasse cellulose bundle crystal is converted to a cellulose few-layer two-dimensional (2D) crystal by a specially designed technique scheme, which consists of (1 → 4)-β-D-glucan chains bound to each other by hydrogen bonds in a plane. A graphene few-layer 2D crystal is fabricated from the cellulose 2D crystal by pyrolysis reaction. The fabricated graphene 2D crystal is further analysed and characterised using scanning electron microscopy, high-resolution transmission electron microscopy (HRTEM), atomic force microscopy, and Raman, X-ray diffraction and X-ray photoelectric spectroscopies. A very clear 2D crystal pattern of graphene is observed in the HRTEM image of the carbon product prepared from the cellulose 2D crystal. As a control, in a parallel experiment, multi-layer graphene (or graphite) is obtained from the cellulose bundle crystal. The following possible mechanism is proposed. During carbonization of the cellulose 2D crystal, the glucose units (C6 H10 O5 )n lose oxygen and hydrogen atoms in the form of water, and the six carbon units (C6 )n reorganise, forming the graphene 2D crystal at the structural basis of the 2D crystal of cellulose. The findings from this study provide an economical and environmentally friendly approach to the fabrication of graphene and extend the applications of sustainable biomass cellulose. Graphical abstract: Image 1044 Highlights: The cellulose bundle crystal was hydrolysed to the few-layer 2D crystal of cellulose. The graphene 2D crystal was successfully fabricated from the cellulose 2D crystal. A clear 2D crystalline pattern was observed in the TEM image of the graphene sample. The most important techniques, from 2D cellulose to 2D graphene, were illustrated. A mechanism from the 2D cellulose crystal to the 2D graphene crystal was proposed.